Identification of a Pseudomonas aeruginosa PAO1 DNA methyltransferase, its Targets, and physiological roles - Doberenz, Sebastian; Eckweiler, Denitsa; Reichert, Olga; Jensen, Vanessa; Bunk, Boyke; Spröer, Cathrin; Kordes, Adrian; Frangipani, Emanuela; Luong, Khai; Korlach, Jonas; Heeb, Stephan; Overmann, Jörg; et al. (American Society for Microbiology, 2017)
DNA methylation is widespread among prokaryotes, and most DNA methylation reactions are catalyzed by adenine DNA methyltransferases, which are part of restriction-modification (R-M) systems. R-M systems are known for their role in the defense against foreign DNA; however, DNA methyltransferases also play functional roles in gene regulation. In this study, we used single-molecule real-time (SMRT) sequencing to uncover the genome-wide DNA methylation pattern in the opportunistic pathogen Pseudomonas aeruginosa PAO1. We identified a conserved sequence motif targeted by an adenine methyltransferase of a type I R-M system and quantified the presence of N(6)-methyladenine using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Changes in the PAO1 methylation status were dependent on growth conditions and affected P. aeruginosa pathogenicity in a Galleria mellonella infection model. Furthermore, we found that methylated motifs in promoter regions led to shifts in sense and antisense gene expression, emphasizing the role of enzymatic DNA methylation as an epigenetic control of phenotypic traits in P. aeruginosa Since the DNA methylation enzymes are not encoded in the core genome, our findings illustrate how the acquisition of accessory genes can shape the global P. aeruginosa transcriptome and thus may facilitate adaptation to new and challenging habitats.IMPORTANCE With the introduction of advanced technologies, epigenetic regulation by DNA methyltransferases in bacteria has become a subject of intense studies. Here we identified an adenosine DNA methyltransferase in the opportunistic pathogen Pseudomonas aeruginosa PAO1, which is responsible for DNA methylation of a conserved sequence motif. The methylation level of all target sequences throughout the PAO1 genome was approximated to be in the range of 65 to 85% and was dependent on growth conditions. Inactivation of the methyltransferase revealed an attenuated-virulence phenotype in the Galleria mellonella infection model. Furthermore, differential expression of more than 90 genes was detected, including the small regulatory RNA prrF1, which contributes to a global iron-sparing response via the repression of a set of gene targets. Our finding of a methylation-dependent repression of the antisense transcript of the prrF1 small regulatory RNA significantly expands our understanding of the regulatory mechanisms underlying active DNA methylation in bacteria.